Teori Belajar Humanistik serta Penerapannya dalam Pembelajaran - Habsy, Bakhrudin All; Nashihah, Durrotun; Atsila, Butsaina Altaf (TSAQOFAH, 2024)
Not just a means of knowledge transformation, but the learning process of humanistic education is part of developing human values. This research uses a literature study method with a descriptive qualitative research type with library research which seeks to describe the role of humanistic learning theory and its application in learning. The theory of humanism, which was initiated by key figures such as Abraham Maslow and Carl Rogers, has the main goal of encouraging human self-development towards autonomous self-actualization. The implementation of humanistic theory in education includes forming students with noble character, motivating students to learn actively, and creating an environment that supports students' positive self-development. The main aim of education by applying humanistic learning theory is to humanize humans.